Deconstructing Sophisticated Greenwashing: A Meta-Synthesis of Sustainability Communication Strategies on Social Media and Their Impact on Consumer Skepticism - Azmi, Fauzan; Irawan, Dika; Primadayani, Syurti; Siregar, Prima Andreas (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
The rise of sophisticated greenwashing on social media has revealed a sharp increase in misleading sustainability communication strategies, triggering consumer skepticism about sustainability claims. This study aims to identify a typology of advanced greenwashing strategies and analyze their impact on consumer skepticism through persuasion, signaling, and attribution theories. Using a literature-based approach, data were gathered from recent academic sources relevant to greenwashing, social media and consumer behavior. The findings indicate that inauthentic sustainability narratives enhance the perception of manipulation, leading to brand distrust. This study proposes a conceptual framework that outlines the relationship between greenwashing tactics, consumers’ cognitive evaluation processes, and the emergence of skepticism in response to non-transparent communication.